Modifications in gene expression and phenolic compounds content by methyl jasmonate and fungal elicitors in Ficus carica. Cv. Siah hairy root cultures - Amani, Shahla; Mohebodini, Mehdi; Khademvatan, Shahram; Jafari, Morad; Kumar, Vinod (BioMed Central, 2024)
Background : One of the most effective strategies to increase phytochemicals production in plant cultures is elicitation. In the present study, we studied the effect of abiotic and biotic elicitors on the growth, key biosynthetic genes expression, antioxidant capacity, and phenolic compounds content in Rhizobium (Agrobacterium) rhizogenes-induced hairy roots cultures of Ficus carica cv. Siah. Methods : The elicitors included methyl jasmonate (MeJA) as abiotic elicitor, culture filtrate and cell extract of fungus Piriformospora indica as biotic elicitors were prepared to use. The cultures of F. carica hairy roots were exposed to elicitores at different time points. After elicitation treatments, hairy roots were collected, and evaluated for growth index, total phenolic (TPC) and flavonoids (TFC) content, antioxidant activity (2,2-diphenyl-1-picrylhydrazyl, DPPH and ferric ion reducing antioxidant power, FRAP assays), expression level of key phenolic/flavonoid biosynthesis genes, and high-performance liquid chromatography (HPLC) analysis of some main phenolic compounds in comparison to control. Results : Elicitation positively or negatively affected the growth, content of phenolic/flavonoid compounds and DPPH and FRAP antioxidant activities of hairy roots cultures in depending of elicitor concentration and exposure time. The maximum expression level of chalcone synthase (CHS: 55.1), flavonoid 3′-hydroxylase (F3’H: 34.33) genes and transcription factors MYB3 (32.22), Basic helix-loop-helix (bHLH: 45.73) was induced by MeJA elicitation, whereas the maximum expression level of phenylalanine ammonia-lyase (PAL: 26.72) and UDP-glucose flavonoid 3-O-glucosyltransferase (UFGT: 27.57) genes was obtained after P. indica culture filtrate elicitation. The P. indica elicitation also caused greatest increase in the content of gallic acid (5848 µg/g), caffeic acid (508.2 µg/g), rutin (43.5 µg/g), quercetin (341 µg/g), and apigenin (1167 µg/g) phenolic compounds. Conclusions : This study support that elicitation of F. carica cv. Siah hairy roots can be considered as an effective biotechnological method for improved phenolic/flavonoid compounds production, and of course this approach requires further research.
Keywords: Fungal elicitor; Hairy roots; Methyl jasmonate; Piriformospora indica; Rhizobium (Agrobacterium) rhizogenes; Secondary metabolites